Telehealth Before and During the COVID-19 Pandemic: Analysis of Health Care Workers' Opinions - Pascal Nitiema (JMIR Publications, 2022)
BackgroundThe COVID-19 pandemic and the lockdowns for controlling the spread of infection have led to a surge in telehealth adoption by many health care organizations. It is unclear how this pandemic has impacted health professionals' view about telehealth. The analysis of textual data, such as comments posted on a discussion forum, can uncover information that may not be captured by a structured survey. ObjectiveThis study aims to examine the opinions of health care workers about telehealth services during the time frame of March 2013-December 2020. MethodsComments about telehealth posted by health care workers from at least 46 countries were collected from an online discussion forum dedicated to health professionals. The analysis included the computation of sentiment scores from the textual data and the use of structural topic modeling to identify the topics of discussions as well as the factors that may be associated with the prevalence of these topics. ResultsThe analysis of the comments revealed positive opinions about the perceived benefits of telehealth services before and during the pandemic, especially the ability to reach patients who cannot come to the health facility for diverse reasons. However, opinions about these benefits were less positive during the pandemic compared to the prepandemic period. Specific issues raised during the pandemic included technical difficulties encountered during telehealth sessions and the inability to perform certain care routines through telehealth platforms. Although comments on the quality of care provided through telehealth were associated with a negative sentiment score overall, the average score was less negative during the pandemic compared to the prepandemic period, signaling a shift in opinion about the quality of telehealth services. In addition, the analysis uncovered obstacles to the adoption of telehealth, including the absence of adequate legal dispositions for telehealth services and issues regarding the payment of these services by health insurance organizations. ConclusionsEnhancing the adoption of telehealth services beyond the pandemic requires addressing issues related to the quality of care, payment of services, and legal dispositions for delivering these services.